Long-term effects of vagus nerve stimulation in refractory pediatric epilepsy: A single-center experience - Yalnızoğlu, Dilek; Ardıçlı, Didem; Bilginer, Burçak; Konuşkan, Bahadır; Karlı Oğuz, Kader; Akalan, Nejat; Turanlı, Güzide; Saygı, Serap; Topçu, Meral (Academic Press Inc Elsevier Science, 2020)
Introduction: Vagus nerve stimulation (VNS) has been used as an adjunctive therapy for both children and adults with refractory epilepsy, over the last two decades. In this study, we aimed to evaluate the long-term effects and tolerability of VNS in the pediatric drug-resistant epilepsy (DRE) and to identify the predictive factors for responsiveness to VNS.Methods: We retrospectively reviewed the medical records of pediatric patients who underwent VNS implantation between 1997 and 2018. Patients with >= 50% reduction of seizure frequency compared with the baseline were defined as "responders". The clinical characteristics of responders and nonresponders were compared.Results: A total of 58 children (male/female: 40/18) with a mean follow-up duration of 5.7 years (3 months to 20 years) were included. The mean age at implantation was 12.4 years (4.5 to 18.5 years). Approximately half (45%) of our patients were responders, including 3 patients (5.8%) who achieved seizure freedom during follow-up. The age of seizure-onset, duration of epilepsy, age at implantation, and etiologies of epilepsy showed no significant difference between responders and nonresponders. Responders were more likely to have focal or multifocal epileptiform discharges (63%) on interictal electroencephalogram (EEG), when compared to nonresponders (36%) (p = .07). Vocal disturbances and paresthesias were the most common side effects, and in two patients, VNS was removed because of local reaction.Conclusion: Our series had a diverse etiological profile and patients with transition to adult care. Long-term follow-up showed that VNS is an effective and well-tolerated treatment modality for refractory childhood onset epilepsy. Age at implantation, duration of epilepsy and underlying etiology are not found to be predictors of responsiveness to VNS. Higher response rates were observed for a subset of patients with focal epileptiform discharges.
Keywords: Vagus Nerve Stimulation; Drug-Resistant Epilepsy; Pediatric